Morphometric Variations of Nile Tilapia (Oreochromis niloticus) (Linnaeus, 1758) (Perciformes, Cichlidae) Collected from Three Rift Valley Lakes in Ethiopia - Berhan Asmamaw; Misikire Tessema (Journal of Aquaculture and Fish Health, 2021)
The pattern of morphometric differentiation among three populations of Tilapia (Oreochromis niloticus) sited in Koka, Ziway, and Langano lakes in the Ethiopian rift valley was examined. Morphometric differentiation was examined, compared and quantified by the use of twelve different body measurements in 391 specimens to generate baseline information for conservation and product improvement plans. The result revealed that comparisons of mean values of morphometric measurements in the three studied tilapia populations statistically significant differences (P<0.05). The Fulton’s condition factor (K) of Oreochromi niloticus samples collected from Lakes Koka, Ziway, and Langano was 1.48, 1.2, and 0.66, respectively. The Discriminant Function Analysis performed on seven variables led to a correct classification in 90.5 % of cases. Differences observed between samples in this study indicated that there is important morphometric variation between the studied tilapia populations. Plotting the two significant canonical discriminant functions separated the Lake Langano population from the other two.